Stereotactic body radiotherapy for lung cancer patients with idiopathic interstitial pneumonias. Issue 2 (November 2017) - Tsurugai, Yuichiro; Takeda, Atsuya; Sanuki, Naoko; Enomoto, Tatsuji; Kaneko, Takeshi; Hara, Yu; Mizuno, Tomikazu; Saeki, Noriyuki; Aoki, Yousuke; Oku, Yohei; Akiba, Takeshi; Kunieda, Etsuo
Abstract: Purpose: To compare toxicity and survival after stereotactic body radiotherapy (SBRT) between lung cancer patients with or without idiopathic interstitial pneumonias (IIPs), and to investigate the potential value of SBRT for the patients. Methods: Among lung cancer patients receiving SBRT between 2005 and 2016, we evaluated those treated with a total dose of 40–60 Gy in five fractions with curative intent who either were staged as cT1-4N0M0 or experienced postoperative isolated local recurrence. We analyzed the incidence of radiation pneumonitis (RP) in all patients and local recurrence and overall survival (OS) in T1a-2a patients. Results: A total of 508 patients were eligible, including 42 with IIPs. The median follow-up was 32.3 (6.0–120.9) months. Significantly more patients with IIPs had grade ≥3 RP than did those without IIPs (12% vs. 3%, p  = 0.009). The 2-year local recurrence rate was low in both groups (3.4% vs. 5.6%, p  = 0.38). The 2-year OS rate was significantly lower in the patients with IIPs (42.2% vs. 80.9%, p  < 0.001), although death from lung cancer was comparable ( p  = 0.74). Conclusion: SBRT achieved excellent local control with acceptable pulmonary toxicity in lung cancer patients with IIPs. SBRT can be a reasonable option for early lung cancer patients with IIPs.